IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP HAK KEKAYAAN INTELEKTUAL MASYARAKAT ASLI/TRADISIONAL DI KABUPATEN PURBALINGGA - Mardiyanto, Agus; Kupita, Weda; Asyik, Noor; Bintoro, Rahadi Wasi (Faculty of Law, Universitas Jenderal Soedirman, 2013)
The regulating of intellectual property rights until now has not accommodate intellectual property of traditional/native societies. In Purbalingga, there are 9 traditional commodity cluster, with a number of industry as much as 150 UKM and from that number only 4 which has been registered as intellectual property rights. The research will discuss to implementation of protection of intellectual property rights and factors that tend to influence the protection of intellectual property rights in Purbalingga regency. The method that applicated in this research was juridical sociological. Based on the study, local government has made protection to intellectual property rights through socialization to the public. However, there were factors that tend to hamper the protection of intellectual property rights, including law enforcer/officer factors, media and facilities factors, community and cultural factors. In the research, researcher suggested that the local government made a cooperation with central of intellectual property rights in college, considering human resources still relatively didn't understand technical drafting of intellectual property rights registration. Keywords: legal protection, intellectual property rights, intellectual property of traditional / native societies